The Role of Hydroxyl Modification of Peptidoglycan to Reduce the TTX Toxicity via Superior Absorption - Chang’e Wang; Yi Guo; Lili Zhang; Junjian Miao; Ying Lu (Foods, 2025)
The by-products that may contain tetrodotoxin (TTX) produced during the processing of farmed pufferfish have caused food safety risks and environmental pollution. Peptidoglycan (PG) of lactic acid bacteria could adsorb TTX; however, its complex structure and poor solubility limited adsorption efficiency. In this study, hydroxyl modifications of three PGs (A3α, A1γ and A4α) were realized via TEMPO-mediated selective oxidation of the primary hydroxyl group. Compared with PGs, it was found that the carboxyl density of hydroxyl-modified PGs (HM-PGs) increased from 1.66 mmol/g to 3.33 mmol/g and the surface electronegativity increased from −36 mV to −59 mV. The adsorption capacity of HM-PGs to TTX reached 1.48 μg/mg, which was comparable to the adsorption of the conventional adsorbent chitosan for aflatoxin B1 (1.39 μg/mg). Moreover, HM-PGs decreased the toxicity of TTX from strong toxic to nearly non-toxic, with the toxicity reduction rate reached 99.85%. After treatment with HM-PGs, the mouse hippocampus and neuronal cell model confirmed that lower neural injury and sodium channel blocking effects were observed in the residual TTX, whose neurotoxicity was lower. Molecular docking simulation and physicochemical analysis revealed that the adsorption of TTX by HM-PGs was a complex adsorption mode driven by the synergy of physicochemical interaction. There were both physical adsorptions based on electrostatic and hydrophobic interactions and chemical binding with strong hydrogen bonding (1.46 Å) and Mayer bond order (0.1229). This study not only developed a new, efficient and safe tool for TTX removal, but also provided a theoretical basis for the development of biological toxin removal material.